Interactions between the regulatory peptide 26RFa (QRFP) and insulin in the regulation of glucose homeostasis in two complementary models: The high fat 26RFa-deficient mice and the streptozotocin insulin-deficient mice. (April 2023) - Le Solliec, Marie-Anne; Arabo, Arnaud; Takhlidjt, Saloua; Maucotel, Julie; Devère, Mélodie; Berrahmoune, Hind; Bénani, Alexandre; Nedelec, Emmanuelle; Lefranc, Benjamin; Leprince, Jérôme; Picot, Marie; Chartrel, Nicolas; et al.
Abstract: The regulatory peptide 26RFa (QRFP) is involved in the control of glucose homeostasis at the periphery by acting as an incretin, and in the brain by mediating the central antihyperglycemic effect of insulin, indicating the occurrence of a close relationship between 26RFa and insulin in the regulation of glucose metabolism. Here, we investigated the physiological interactions between 26RFa and insulin in two complementary models i.e. a model of obese/hyperglycemic mice deficient for 26RFa and a model of diabetic mice deficient for insulin. For this, transgenic 26RFa-deficient mice were made obese and chronically hyperglycemic by a 3-month high fat diet (HFD) and second group of mice was made diabetic by destruction of the β cells of the pancreatic islets using a single injection of streptozotocin. Our data reveal that 26RFa deficiency does not impact significantly the "glycemic" phenotype of the HFD mice. The pancreatic islets, liver, white adipose tissue masses are not altered by the lack of 26RFa production but the brown adipose tissue (BAT) weight is significantly increased in these animals. In diabetic insulin-deficient mice, the injection of 26RFa does not exhibit any beneficial effect on the impaired glucose homeostasis characterizing this model. Finally, we show that streptozotocin diabetic mice display lowered plasma 26RFa levels as compared to untreated mice, whereas the expression of the peptide in the duodenum is not affected. Taken together, the present results indicate that dysregulation of glucose homeostasis in obese/hyperglycemic mice is not aggravated by the absence of 26RFa that may be compensated by the increase of BAT mass. In diabetic insulin-deficient mice, the antihypergycemic effect of 26RFa is totally blunted probably as a result of the impaired insulin production characterizing this model, avoiding therefore the action of the peptide.